Overt Acute Hepatitis B Deteriorates in Females: Destructive Immunity With an Exaggerated Interleukin-17 Pathway - Chang, Ming-Ling; Yeh, Chau-Ting; Chien, Rong-Nan; Liaw, Yun-Fan (Frontiers in Immunology, 2021)
Background and Aims We previously showed that overt acute hepatitis B (AHB) was more severe in female patients. Using the same cohort and AHB mouse model, we examined the underlying mechanism. Methods Baseline biochemistry, virological and cytokine assays, and T helper (Th)1 and Th2 immune markers of 118 consecutive patients were analyzed. The decompensated livers of AHB and chronic hepatitis B (CHB) patients who underwent liver transplantation were analyzed immunohistochemically. B6 mice were hydrodynamically injected with pHBV1.3 plasmids. Results Decompensated AHB patients (n=41) were older, more often female, and had higher alanine aminotransferase (ALT), soluble programmed cell death protein 1 (sPD-1) levels, and neutrophil-lymphocyte ratios but lower rates of HBeAg positivity and quantitative HBsAg, interferon (IFN)-γ-inducible protein 10 (IP-10), IFN-γ, and interleukin-4 (IL-4) levels than the compensated patients. Female sex (95% CI OR=1.07 54.9), age (1.06 1.40), and ALT levels (1.001 1.004) were associated with hepatic decompensation. Higher sPD-1 but lower IFN-γ and IL-4 levels were observed in female patients. Compared to CHB, decompensated AHB livers had more IL-17-positive cells but fewer HBsAg-positive cells and lower CD4/CD8 ratios. Higher serum IL-17 levels were noted in the female AHB mice than those in the males. Conclusions Females predominated in decompensated AHB, in which downregulated IFN-γ and IL-4 with augmented hepatic IL-17-positive cell development indicated accelerating destructive immunity to enhance viral clearance. The early surge of serum IL-17 was confirmed in the female AHB mice. Targeting the pathway involving IFN-γ, IL-4, and IL-17 might prevent liver transplantation or fatality in decompensated AHB.